1997
DOI: 10.1021/bp960093h
|View full text |Cite
|
Sign up to set email alerts
|

Mist Deposition onto Hairy Root Cultures: Aerosol Modeling and Experiments

Abstract: We analyzed the applicability of the standard models for aerosol deposition in randomly packed fibrous filter beds to mist deposition across a bed of hairy roots in the nutrient mist bioreactor. Although the assumptions inherent in the models are met on a local level, the overall structure of the root bed introduces some uncertainty into the correct choice of root packing fraction and gas velocity required by the model. For reasonable parameter values, the minimum in the deposition efficiency curves is close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…Although root beds have regions of high and low packing density and growth occurs in all directions, the model still describes the qualitative trends and behavior of mist deposition quite reasonably. Deposition experiments using manually packed root beds with a ¼ 0.5, showed that the model matched the experimental data quite well as long as the Reynolds number (Re) was <10 (Wyslouzil et al, 1997). The Reynolds number characterizes the relative importance of inertial and viscous forces during fluid flow, and for filtration problems:…”
Section: Results and Discussion Increased Packing Fraction Increases mentioning
confidence: 83%
See 3 more Smart Citations
“…Although root beds have regions of high and low packing density and growth occurs in all directions, the model still describes the qualitative trends and behavior of mist deposition quite reasonably. Deposition experiments using manually packed root beds with a ¼ 0.5, showed that the model matched the experimental data quite well as long as the Reynolds number (Re) was <10 (Wyslouzil et al, 1997). The Reynolds number characterizes the relative importance of inertial and viscous forces during fluid flow, and for filtration problems:…”
Section: Results and Discussion Increased Packing Fraction Increases mentioning
confidence: 83%
“…In the current experiments, the Reynolds number was in the range of 5.29 < Re < 9.93, and the tube dimensions were similar to those used by Wyslouzil et al (1997).…”
Section: Results and Discussion Increased Packing Fraction Increases mentioning
confidence: 98%
See 2 more Smart Citations
“…Of course, this represents only one of three factors that de Dios Rivera (2011) and others (Rajaram et al, 2016;Ritter, 2016, 2017) consider to represent the overall efficiency. Descriptions of the capture efficiency, η capt , as can be found in Regalado and Ritter (2016) are based upon work by Wyslouzil et al (1997), Friedlander (2000, Demoz et al (1996) and Davidson and Friedlander (1978). Regalado and Ritter (2016) illustrates a result for the droplet capture efficiency of a single cylindrical strand as ) is the dynamic viscosity of the air, and d (m) is the diameter of the assumed cylindrical screen elements.…”
Section: Discussionmentioning
confidence: 99%